Performance of a token-passing system with batch arrivals and its application to file transfers - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 1993)
This paper investigates the performance of token-passing systems with limited service and Poisson arrivals. For pure Poisson arrivals, the Laplace-Stieltjes Transform (LST) of an approximate customer/packet waiting time distribution is derived and expressed as a functional equation, from which the approximate mean and variance of waiting time are obtained; for batch Poisson arrivals, an approximate mean of waiting time is derived. Mean waiting time approximations are compared against both simulation results and other results presented in the literature; the variance approximation is evaluated by comparing it to simulation results only, since no other results on variance have been reported so far. As application examples of our analytical results, multimedia file transfers over token-passing LANs are modelled and studied.